PTH-056 Productive Endoscopy Project. (9th June 2014) - Taggart, N; Lucking, J; Eccles, C; Cooper, C; Kennedy, K; Daw, D; Williams, L; Hymer, W; Mcguinness, D; Flavell, L; Dahill, J; Sarkar, S
Abstract : Introduction: In June 2012 the Royal Liverpool endoscopy department was chosen by NHS Improving Quality to be a pilot site for the development and implementation of a productive endoscopy toolkit. The outcome was improved efficiency, safety, patient experience and team-working. Methods: The aim was to apply processes and cultures of lean thinking to endoscopy and complete a series of modules that increase safety, reliability of care, improve team performance and improve efficiency. A six month "diagnostic phase" involved collecting data on all aspects of the service to identify areas for improvement. A number of modules were completed that tackled the inefficiencies identified and involved the engagement of all staff groups. Results: Stock: The "well organised unit" module identified £7, 500 of redundant stock. Clearing the extra space meant equipment could be re-allocated, releasing two bed spaces in recovery. Enemas: 44% of patients were not compliant with their enemas. Of the 56% who were complaint 14% was ineffective. This impacted on the daily running of the department due to un-prepped patients. This has led to a different type of enema now being used along with the development of more detailed patient information. Department efficiency: Start/ Stop audit identified that 15% of the time, rooms were not utilised and 85% of time the list started late, due to staff or the room not being ready for the start of the morning session. Sharing this information with the teams led to more motivation and demonstrable leadership by senior Clinicians and Nursing staff to improve workforce compliance. 50% of lists finished late, 43% was due to complex procedures over-running this has led to stricter vetting and more points allocated for these procedures. Further data analysis has shown that Thursday and Friday run late 65% of the time due to endoscopists arriving late for the start of the afternoon session because of over-run clinics. This has led to a review of the scheduling template. Patient experience: Long waits were problematic for patients particularly, time after admission, prior to procedure, patients waited 12 to 90 mins and time spent post procedure, waiting for discharge, up to 210 mins. Discharges were also slower in the afternoon than in the evening. Review of skill mix and assigning specific roles to discharge will help to expedite effective and timely discharge. Conclusion: Working through the innovative tools and processes of each module has allowed us to use an evidence based methodology for quality improvement. The use of advanced data collection has highlighted clearly what improvements are needed based upon facts and not assumptions. Disclosure of Interest: None Declared.